2012
DOI: 10.2147/jmdh.s33740
|View full text |Cite
|
Sign up to set email alerts
|

What is optimal timing for trauma team alerts? A retrospective observational study of alert timing effects on the initial management of trauma patients

Abstract: BackgroundTrauma teams improve the initial management of trauma patients. Optimal timing of trauma alerts could improve team preparedness and performance while also limiting adverse ripple effects throughout the hospital. The purpose of this study was to evaluate how timing of trauma team activation and notification affects initial in-hospital management of trauma patients.MethodsData from a single hospital trauma care quality registry were matched with data from a trauma team alert log. The time from patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…The arrival of a patient with suspected severe injury by EMS is usually pre-announced in European countries and a team assembled in the trauma room, including specialists for Surgery, Anesthesiology and Radiology. Given the delay in diagnostic procedures, the lack of announcement may lead to a delay in alarming the team, as early trauma team activation leads to accelerated diagnostic measures [ 18 ]. In contrast, EMS transport may increase vigilance upon in-hospital treatment and thus accelerate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The arrival of a patient with suspected severe injury by EMS is usually pre-announced in European countries and a team assembled in the trauma room, including specialists for Surgery, Anesthesiology and Radiology. Given the delay in diagnostic procedures, the lack of announcement may lead to a delay in alarming the team, as early trauma team activation leads to accelerated diagnostic measures [ 18 ]. In contrast, EMS transport may increase vigilance upon in-hospital treatment and thus accelerate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have shown that timely trauma system activation improves the trauma team performance as measured by time to chest radiograph. 16 However, it has further been determined that proactive trauma team activation and subsequent early trauma team arrival and mobilization of resources has no effect on ED length of stay and mortality in most patients. 16 , 17 Yet despite no noted increase in ED length of stay, early trauma team activation may be important in select cases such as when multiple trauma patients arrive simultaneously or for stroke and myocardial infarction cases when door-to-needle time could potentially be shortened.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies alluded to the fact that manually recorded data are subject to the human propensity to smoothen data. 16 , 27 For future studies, it may be beneficial for the trauma registry to move toward automatic capturing of time data.…”
Section: Limitationsmentioning
confidence: 99%
“…Time is a key predictor of clinical outcomes in the critically injured patient. Timely out‐of‐hospital notifications from emergency medical services (EMS) transporting trauma patients are associated with decreased mortality, more rapid interventions in the emergency department (ED), and a shortened hospital length of stay 1‐3 . The importance of time is magnified in traumatic cardiac arrest, where the duration of out‐of‐hospital resuscitation predicts survival and is a critical factor in selecting appropriate patients for resuscitative procedures 4‐6 .…”
Section: Introductionmentioning
confidence: 99%